Climate change and the welfare state? Exploring Australian attitudes to climate and social policy - Spies-Butcher, Ben; Stebbing, Adam (Journal of Sociology, 2016)
Despite growing evidence of significant impacts from human-induced climate change, policy responses have been slow. Understanding this policy inertia has led to competing explanations, which either point to the need to build a consensual politics separated from economic partisanship, or which encourage solidarities between environmental and social movements and issues. This article analyses a recent successful mobilisation, leading to the passage of the Clean Energy Act in Australia, to explore the relationship between attitudes to environmental and social protection, particularly among the core constituency in favour of stronger climate action. Using social survey data from the Australian Election Study, the article finds evidence of independent associations between prioritising environmental concerns and support for welfare state expansion, and a realignment of materialist and post-materialist values. This we argue is consistent with Polanyian analysis that posits a link between social and environmental causes based on resistance to commodification.
Sociology
Keywords: clean energy; climate policy; climatic changes - government policy; commodification; law and legislation; political attitudes; social policy; welfare state

How Will Capitalism End?: Essays on a Failing System - Streeck, Wolfgang (Verso Books, 2016)
The provocative political thinker asks if it will be with a bang or a whimperAfter years of ill health, capitalism is now in a critical condition. Growth has given way to stagnation; inequality is leading to instability; and confidence in the money economy has all but evaporated.In How Will Capitalism End?, the acclaimed analyst of contemporary politics and economics Wolfgang Streeck argues that the world is about to change. The marriage between democracy and capitalism, ill-suited partners brought together in the shadow of World War Two, is coming to an end. The regulatory institutions that once restrained the financial sector’s excesses have collapsed and, after the final victory of capitalism at the end of the Cold War, there is no political agency capable of rolling back the liberalization of the markets.Ours has become a world defined by declining growth, oligarchic rule, a shrinking public sphere, institutional corruption and international anarchy, and no cure to these ills is at hand.
Sociology; Political Science
Keywords: political science / globalization; political science / political economy; political science / political ideologies / democracy

The Power of Market Fundamentalism. Karl Polanyi’s Critique - Silva Baptista, António L. (Analise Social, 2016)
Sociology
Keywords: BLOCK; Fred L.; SOMERS; Margaret R.; The Power of Market Fundamentalism: Karl Polanyi's Critique; The (Book); capitalism; nonfiction; review

'Socialist Accounting' by Karl Polanyi: with preface 'Socialism and the embedded economy' - Bockman, Johanna; Fischer, Ariane; Woodruff, David (Theory & Society, 2016)
Ariane Fischer, David Woodruff, and Johanna Bockman have translated Karl Polanyi's 'Sozialistische Rechnungslegung' ['Socialist Accounting'] from 1922. In this article, Polanyi laid out his model of a future socialism, a world in which the economy is subordinated to society. Polanyi described the nature of this society and a kind of socialism that he would remain committed to his entire life. Accompanying the translation is the preface titled 'Socialism and the embedded economy.' In the preface, Bockman explains the historical context of the article and its significance to the socialist calculation debate, the social sciences, and socialism more broadly. Based on her reading of the accounting and society that Polanyi offers here, Bockman argues that scholars have too narrowly used Polanyi's work to support the Keynesian welfare state to the exclusion of other institutions, have too broadly used his work to study social institutions indiscriminately, and have not recognized that his work shares fundamental commonalities with and often unacknowledged distinctions from neoclassical economics.
Sociology; Political Science
Keywords: Keynesian economics; Keynesianism; embeddedness; neoclassical economics; social accounting; socialism; socialist accounting; socialist calculation debate; welfare state

Polanyi, political-economic opportunity structure and protest: capitalism and contention in the post-communist Czech Republic - Císař, Ondřej; Navrátil, Jiří (Social Movement Studies, 2016)
Drawing on Polanyian logic, we focus on the gradual institutionalization of capitalism in the Czech Republic and the protests accompanying this process. We hypothesize that different configurations of political economy, or what we term the political economic opportunity structure, trigger different popular responses and are a potent indicator of expected protest forms. To analyze this we chose to carry out a country case study, in which many variables commonly associated with political mobilization, in particular the state’s institutional structure, are kept constant. By contrast, models of political economy vary over time, as a function of the extent and form of the international integration of capitalism. We focus on three configurations of political economy – national, globalized and austerity models – and for each one, identify the characteristics and mechanisms, i.e. concrete policy measures, that shape particular protest patterns in the context of our case study. In theoretical terms, this paper seeks to present one possible response, in this case a Polanyian response, to recent complaints about the disappearance of capitalism from social movement studies. At the same time, given the focus of this special issue, our goal is to analyze the current wave of anti-austerity protest that emerged in relation to what has been labelled the Great Recession.
Sociology; Economics
Keywords: Czech Republic; anti-austerity; economic protest; political economic opportunity structure; political opportunity structure; social movement studies

Formal Economy, Substantive Economy, and Economism - Sobel, Richard; Postel, Nicolas (Philosophy of the Social Sciences, 2016)
Polanyi analyzes the historical deployment of a “formal” economic science starting from the “market-scarcity-instrumental rationality triptych.” This triptych, and the knowledge associated with it, is shown to be more than merely a “substantial” economic science’s interest in the triptych “need-nature-institution.” While we must agree with Polanyi that economism is ill-suited to the first triptych, we hesitate to accept his suggested alternative, a heterogeneous mixture of naturalism and institutionalism, essentialism and historicism.
Sociology; Economics
Keywords: capital shortages; capitalism; economic systems; economism; essentialism (philosophy); formal economy; historicism; institutionalism (religion); profit; rationality; scarcity; substantive economy

Globalization and Its Countermovement: Marxian Contention or Polanyian Resistance? - Gemici, Kurtuluş; Nair, Manjusha (Sociology Compass, 2016)
This article surveys the scholarship on the countermovement against the diffusion of capitalism and market economy in the Global South. We identify two streams of analysis in the literature. On the one hand, scholars observe contentious politics instances where the spread of capitalist production relations enables the associational capacity and bargaining power of social classes. On the other hand, there are voluminous studies on contentious politics in the Global South where groups such as peasants, shopkeepers, and urban poor resist the intensification of the market economy. We use Beverly Silver's distinction between Marx-type and Polanyi-type protests, which focuses on how globalization makes and unmakes social groups, to unpack the heterogeneity of the impacts and experiences of globalization. We argue that although Silver's distinction is of great analytical value, there are strong warrants for separating the effects of the market economy from capitalism in studying contentious politics against globalization. Such an analytical strategy (i) expands the scope of the distinction between Marxian and Polanyian contention to social groups other than the working class and (ii) emphasizes that the roots of these struggles lie in the interconnected diffusion of capitalism and market economy.
Sociology
Keywords: Global South; MARX; Karl; 1818-1883; SILVER; Beverly; countermovement; global south; globalization

Apple, Foxconn, and Chinese workers’ struggles from a global labor perspective - Pun, Ngai; Shen, Yuan; Guo, Yuhua; Lu, Huilin; Chan, Jenny; Selden, Mark (Inter-Asia Cultural Studies, 2016)
To enrich the discussion of global labor, between 2010 and 2016, we studied Apple’s value chain, Foxconn’s mode of labor control, and Chinese workers’ struggles. Through our fieldwork in China we also examined Apple’s and Foxconn’s responses to the spate of worker suicides, workers’ resistance, the activism of scholar and student groups, and transnational justice campaigns. We conclude with reflection on global labor studies in light of the debates between Karl Polanyi’s counter movement and Karl Marx’s class-based struggle.
Sociology; Asia Studies
Keywords: Apple; Apple Inc.; China; Chinese workers; Foxconn; Foxconn Technology Group (Company); MARX; Karl; 1818-1883; POLANYI; Karl; 1886-1964; countermovement; global labor studies; global labour studies; student and scholar activism; value chains; working class

The Commonalities of Global Crises: Markets, Communities and Nostalgia - Karner, Christian; Weicht, Bernhard (Springer, 2016)
Bringing together contributions from an international group of social scientists, this collection examines diverse crises, both historical and contemporary, which implicate market forces, widening inequalities, social exclusion, forms of resistance, and ideological polarisation. The Commonalities of Global Crises offers carefully researched case studies which stretch across large geographical distances- from Egypt to the US and from northern, central, eastern and southern Europe to South America- and covers timely issues including human rights, slavery, care, migration, racism, and the far right. The volume demonstrates that such different settings and diverse concerns are characterized by a common tension in which the crises that unfold around pressures of widening marketization and commodification are met by the (re)building or re-assertion of various communities, and competing politics of solidarity and nostalgia.
Sociology; Political Science
Keywords: business & economics / general; commodification; disembedding; double movement; economic theory; political science / general; social science / general

Karl Polanyi and twenty-first century socialism - Block, Fred (openDemocracy, 2016)
Polanyi’s views were the exact opposite of his contemporary, Joseph Schumpeter, who famously defined democracy as giving people a choice over which elite group would rule over them.
Sociology
Keywords: socialism

Public Capital and the Post-Communist Welfare State: The Case of Poland - Rae, Gavin (Polish Sociological Review, 2016)
This paper provides an overview of some of the main theories of the welfare state. It builds upon Polanyi's theory of the double-movement and relates this to Bourdieu's concept of multiple capitals. It argues that the welfare state can be understood as a form of public capital, both in an economic and sociological sense. The welfare state emerges and is maintained due to a social countermovement that at least partly removes areas of socio-economic life out of commodity relations. In turn this creates public capital, which is both economic and social. In the post-Communist countries most of this public capital was created during a period when almost the whole of economic and social life was controlled by the state. Once the Communist system collapsed, so the accompanying policy of full-employment and system of social welfare organised through state enterprises disappeared. This was met with a large rise in unemployment and labour deactivation, meaning that many social benefits were created during the initial years of the transition. Also, the post-Communist systems inherited large amounts of public capital in the form of public services such as health and education. Through the example of Poland this paper analyses how this public capital was initially maintained and even developed during the early transition period, but then how a process of commodifying it was later begun.
Sociology
Keywords: BOURDIEU; Pierre; 1930-2002; Poland; capital; communism; countermovement; post-communism; public welfare; social movements; social policy; social services; welfare state

Polanyi’s ‘substantive approach’ to the economy in action? Conceptualising social enterprise as a public health ‘intervention’ - Roy, Michael J.; Hackett, Michelle T. (Review of Social Economy, 2016)
For several decades now, critical public health researchers have highlighted the deleterious effects that pursuing neoliberal policies can have on the ‘causes of the causes’ of poor health and upon growing health inequalities. This paper argues that the conceptual tools of Karl Polanyi can help lend particular insight into this issue. The specific example that this paper focuses upon is the ‘social enterprise’: a form of organisation that combines both social and business objectives. The paper explores, conceptually, whether social enterprises may have the potential to act as one component of a neo-Polanyian countermovement: helping to re-embed the economy back into society, and offering greater recognition for a more comprehensive and socially imbued concept of health. Importantly, this potential is critically examined in the context of neoliberal hegemony, where challenges to the status quo have regularly been met with assimilation, co-option and/or repression.
Sociology
Keywords: health inequality; public health; social enterprise; substantive approach

England's Great Transformation: Law, Labor, and the Industrial Revolution - Steinberg, Marc W. (University of Chicago Press, 2016)
With England’s Great Transformation, Marc W. Steinberg throws a wrench into our understanding of the English Industrial Revolution, largely revising the thesis at heart of Karl Polanyi’s landmark The Great Transformation. The conventional wisdom has been that in the nineteenth century, England quickly moved toward a modern labor market where workers were free to shift from employer to employer in response to market signals. Expanding on recent historical research, Steinberg finds to the contrary that labor contracts, centered on insidious master-servant laws, allowed employers and legal institutions to work in tandem to keep employees in line. Building his argument on three case studies—the Hanley pottery industry, Hull fisheries, and Redditch needlemakers—Steinberg employs both local and national analyses to emphasize the ways in which these master-servant laws allowed employers to use the criminal prosecutions of workers to maintain control of their labor force. Steinberg provides a fresh perspective on the dynamics of labor control and class power, integrating the complex pathways of Marxism, historical institutionalism, and feminism, and giving readers a subtle yet revelatory new understanding of workplace control and power during England’s Industrial Revolution.
History; Economics; Sociology
Keywords: business & economics / economic history; economic history; history / Europe / Great Britain; history / general; industrial revolution; social science / sociology / general

Fair trade certification as oversight: an analysis of fair trade international and the small producers' symbol - Clark, Patrick; Hussey, Ian (New Political Economy, 2016)
In this article we analyse Fair Trade as a form of non-state regulation, building on the literature on the internal politics and governance of Fair Trade International (FTI) certification. We focus on recent developments in the FTI certification system, including the split of Fair Trade USA from FTI and the emergence of the Small Producer's Symbol (SPP) as an alternative to FTI certification. We highlight the role of the three regional Producer Networks, in particular the Latin American Producer Network, the CLAC, in the politics and governance of the FTI system. In order to analyse these issues we employ an alternative reading of Karl Polanyi's work in relation to Fair Trade. We problematise the claim made by some in the literature that FTI certification is an example of Polanyi's concept of re-embedding. Instead, we draw on Polanyi's concept of oversight to analyse Fair Trade certification. We argue that the emergence of the SPP out of the CLAC shows promise for being a mechanism of oversight more reflective of Polanyian re-embedding than FTI certification. We also emphasise how the growth of the SPP and the pressure from the Producer Networks have prompted governance reform within the FTI system.
Political Science; Sociology
Keywords: Canada; Carleton University; European Union countries; certification; economic conditions; fair trade; financial crises; financial crisis; governance; liberalization (finance); municipal services; producer networks; small producers; unfair competition

Neoliberalism, Polanyi's Protective Response, and Veblenian Waste - Wrenn, Mary V. (Journal of Economic Issues (Taylor & Francis Ltd), 2016)
As capitalism unfolds, continual technological advance – in combination with the relentless accumulation imperative – serves to amplify material progress. The expanding economic sphere begins to pervade the everyday lives and thinking of the individual. The institutionalization of the market fundamentally changes the structure of society and, in so doing, fundamentally changes the institutional structure through which individuals are socialized. The social dislocation generated therein prompts Karl Polanyi's protective response. Despite this market intensification, the existence of the economic surplus undermines the syllogistics of market-determined pricing. Evidence of the economic surplus and Veblenian waste as well as of the fact that the competitive law of value is not operable under neoliberalism is found in the lobby industry and campaign contributions. This research seeks to explicitly connect the concepts of Polanyi's protective response with Veblenian waste and the economic surplus in order to better understand how the irrational system of neoliberalism continues to evolve.
Sociology; Economics
Keywords: Veblen; capitalism; economic sociology; economic surplus; institutional economics; neoliberalism

Saving the Commons in an Age of Plunder - Batt, H. William (American Journal of Economics and Sociology, 2016)
Land ownership, as commonly understood today, originated with the enclosure movement during the English Tudor era almost four centuries ago. Karl Polanyi referred to this “propertization” of nature as the “great transformation.” That land, water, and air was a social commons is now archaic and forgotten, and with it the classical economic concept of rent, which was, in theory, once paid to royalty as the earth's guardian. Garrett Hardin's article, “The Tragedy of the Commons,” raised alarm about the abuse and loss of this realm, and he recommended constraints and privatization to prevent this. Most people view titles to landed property much as they do their household goods, but Henry George saw that the earth should be seen as a common resource and its value taxed to benefit everyone. This would restore economic equilibrium to market exchanges and pay for government services. The capture of natural resource rents can supplant taxes on wages and capital goods, and it comports with all textbook principles of sound tax theory. This policy can be the modern replacement for the commons, and implementing resource rent capture is both economically and technically feasible.
Economics; Sociology
Keywords: commons; propertization of nature

Az „új közgazdaságtanról” - Polányi Károly kölcsönbe vett szemüvegén keresztül... (Heurisztika és program) - Balázs, Krémer (Szociologiai Szemle, 2016)
This paper aims at interpreting Polanyi's theory on substantive and embedded economy as a possible insight to interpret rich empirical findings of “new economics”. Key phenomena and concepts of Polanyi, especially the “latent commodities” may provide new explanations on how inappropriate political regulations and social conventions biased the integration of land (natural resources), labor and money into past-decades markets, and how led to crises. As a hypothesis the paper suppose more about the relevance of Polanyi's theory by contributing to overcome the crisis of the sociology. Mainstream economic, social and human sciences seek how human and social nature causes biases and fallacies in market mechanisms. Following Polanyi's inspirations, the question should be reversed: the sociological question is not how society impact markets, but rather, how markets contribute to substantive and embedded economy, both on micro (household) and macro (markets, redistribution-welfare state, and reciprocity - new kinships and civic society) levels. (English)
Sociology
Keywords: Polányi; beágyazódottság; embedded economy; substantive economy; szubsztantív gazdaság; új közgazdaságtan

Beyond the Minsky and Polanyi Moments - Gemici, Kurtuluş (Politics & Society, 2016)
The period of very high foreclosure rates sets the 2007–8 financial meltdown apart from similar banking crises fueled by asset price booms. Why did the 2007–8 meltdown lead to a prolonged foreclosure crisis? Through a theoretical perspective built on Minsky’s financial instability hypothesis, Polanyi’s ideas about adverse consequences of commodity fiction, financialization of homes, and institutional coupling, I argue that commodifying houses as financial assets exposed mortgage loan holders to price fluctuations originating in capital markets and elevated their risk of default. I show how increased exposure to price fluctuations followed from the tight coupling between U.S. housing and capital markets, a coupling that resulted directly from the rising preponderance of securitization in U.S. housing finance. I provide further evidence from countries where housing finance was tightly coupled with capital markets (Iceland and Ireland) to countries where housing finance did not rely dominantly on capital markets (Canada and the Netherlands).
Sociology
Keywords: MINSKY; Hyman; United States; asset-backed financing; economic aspects; financial instability; financialization; foreclosure; great recession; housing foreclosures; institutional coupling; recessions - 2008-2013; securitization

The New Urban Fiscal Crisis - Kirkpatrick, L. Owen (Politics & Society, 2016)
Numerous U.S. cities suffered immense fiscal strain following the subprime mortgage crisis and financial crash of 2007–8. Diminished revenues, tightened credit, and speculative financing that went bad in the aftermath fueled widespread fiscal distress on the local scale. Although the current moment resembles fiscal crises that crested in cities in the 1970s–90s, two factors distinguish the current period. First, municipal affairs have become thoroughly financialized—dominated by speculative securities and volatile debt arrangements—such that local crisis can no longer be understood apart from financial market instability. Second, local fiscal politics have become increasingly removed from democratic oversight and control. This de-democratization hinders the capacity of political communities to reregulate markets and rebuild urban communities. An analytic model derived from the work of Hyman Minsky and Karl Polanyi emphasizes how cities become ensnared in a “financial instability” cycle and how communities seek to protect themselves by way of the “double movement.”
Sociology
Keywords: Chicago; Detroit; MINSKY; Hyman; United States - economic conditions; de-democratization; financialization; municipal bonds; municipal finance; recessions - 2008-2013; urban fiscal crisis

The contradictory logics of financialization: Bringing together hyman minsky and Karl Polanyi - Block, F. (Politics and Society, 2016)
This introduction explains the logic of bringing together the perspectives of Hyman Minsky and Karl Polanyi to analyze processes of financialization. Although Minsky and Polanyi have very different intellectual trajectories, there are important complementarities in their approaches. The introduction also explains the focus of the three papers in this special section written by Kurtuluşc Gemici, Lucas Kirkpatrick, and David Woodruff. © 2015 SAGE Publications.
Sociology
Keywords: MINSKY; Hyman; finance; financial crises; financial crisis; financialization; political economy; speculation

Treble Troubles? Marketization, Social Protection and Emancipation Considered Through the Lens of Slavery - Davidson, Julia O’Connell (The Commonalities of Global Crises, 2016)
This chapter considers white European and American thinking on transatlantic slavery historically and, more briefly, in relation to today’s antislavery movement. Combining historical longue durée and a critical engagement with Nancy Fraser’s neo-Polanyian position, O’Connell Davidson shows that abolitionists were, and are, hard to fix as proponents of either market freedom or social protection, or indeed of ‘emancipation’. The postabolition experience of freed slaves shows that marketization, social protection and emancipation are not fully disarticulable political forces, suggesting that the idea of the ‘triple movement’ may be less useful for those committed to a politics of nondomination than it may initially appear.
Sociology; Political Science
Keywords: economics; public choice; slavery; social choice; social inequality; social protection; social structure; triple movement; welfare economics

Domesticating the market: moral exchange and the sharing economy - Fitzmaurice, Connor; Ladegaard, Isak; Attwood-Charles, William; Cansoy, Mehmet; Carfagna, Luka; Schor, Juliet; Wengronowitz, Robert (Under review at Socio-Economic Review, 2016)
The sharing economy has generated enormous excitement with its promise of transforming work and consumption through technology and novel socio-economic relations. However, critics see the phenomenon as a further development of neoliberalism. Platforms such as Airbnb and TaskRabbit, monetize a previously uncommodified realm of life via renting of bedrooms, possessions, space and labor time. In this paper, we analyze the meanings and attitudes of sharing economy participants. On the basis of 100 interviews in two for-profit and three not-for-profit sites, we find that most see the sharing economy as an opportunity to build a radically different market, from the bottom up. They are critical of the neoliberal market order, and envision an economy of personalized exchanges that are morally attuned, based on ideals of community, and that help them achieve creative and financial autonomy in their working lives. To our respondents, the sharing economy is an opportunity to domesticate the market.
Sociology
Keywords: domestic production; economic sociology; hostile worlds; markets; morality; neoliberalism; sharing economy

Local Embeddedness - Pickles, John (International Encyclopedia of Geography: People, the Earth, Environment and Technology, 2016)
In economic geography and economic sociology, embeddedness refers to the ways in which relational, institutional, and cultural contexts shape economic life. In contrast to the undersocialized and utilitarian assumptions of neoclassical economics, rational choice theory, and new institutional economics, theories of embeddedness focus on the ways in which markets and society are variously articulated in particular societies, organizations, and places. Embeddedness in this sense is associated first and foremost with the work of Karl Polanyi. Polanyi argued that the market generally sought to disembed itself from social regulation, while society responded by attempting to socialize and regulate (re-embed) the excesses of unregulated markets. It is also associated with the work of Granovetter in economic sociology, who cautioned against oversocializing, as well as undersocializing, the economy, in favor of a much more detailed analysis of the specific ways in which social relations structured economic practices.
Geography; Sociology
Keywords: POLANYI; Karl; 1886-1964; culture; economy; embeddedness; institutions; society; undersocialized

Cucumbers and Courgettes: Rural Workfare and the New Double Movement in Hungary - Hann, Chris (Intersections. East European Journal of Society and Politics, 2016)
The paper is an application of the economic anthropology of Karl Polanyi to contemporary rural Hungary. After addressing the influence of Polanyi’s critique of market society and his standing in the discipline of anthropology, the main focus is the community of Tázlár on the Danube-Tisza interfluve. The paper traces the history of the ‘fictitious commodities’ of land and labour in this relatively isolated settlement, which was not fully integrated into the national society until the socialist era. The innovative symbiosis of household and cooperative farming was destroyed in the 1990s. In the depressed economic climate of today, workfare schemes are popular because they treat villagers as human beings rather than as commodities to be exploited for maximum profit. The workfare initiatives of populist power holders can be interpreted as one facet of a complex ‘double movement’ in which postsocialist society seeks to defend itself against the domination of the market.
Publisher: MTA Társadalomtudományi Kutatóközpont Kisebbsegkutató Intézet
Keywords: (post)socialism; Danube-Tisza interfluve; Hungary; Karl Polanyi; double movement; fictitious commodities; neoliberalism; workfare

Embeddedness, Redistribution and Double Dependence: Polányi-reception Reconsidered - Lengyel, György (Intersections. East European Journal of Society and Politics, 2016)
This article – a modified version of a lecture – is a contribution to the reception of Polányi in the West and the East, more precisely, to the inquiry about what impact Polányi’s views have had on American and Hungarian economic sociology, which are the contact points between the two, and what research perspectives they offer. It concentrates on the perception of embeddedness and redistribution, not touching on other views unless they are conducive to the comprehension of certain connections. Polányi’s oeuvre is so rich and it has inspired such a wide range of debates that a conclusive review is impossible within a single article. It is hoped however that the polemic on the concept of embeddedness may be illuminating and also the aftermath of the forms of integration, particularly redistribution, important. The concept of double dependence is touched upon as well, for it grasps an essential feature of the post-socialist Eastern European economies. It is worth mentioning it in this context, for Polányi’s influence left its mark upon it and it is also related to the conceptual apparatus of the substantive view.
Publisher: MTA Társadalomtudományi Kutatóközpont Kisebbsegkutató Intézet
Keywords: Polányi; dependent market economy; double dependenc; embeddedness; fictitious commodities; forms of integration; post-socialist transformation; redistribution; state socialism; varieties of capitalism